Providing social services in Romania, during the pandemic generated by Coronavirus - Sicrea, Cosmin; Chirugu, Gianina (Technium Social Sciences Journal, 2022)
The purpose of this paper is to analyze the influence of the pandemic on the provision of social services in Romania that have experienced a development only in recent years, so the institutional organization at central level contributed to the elaboration of the first legislative regulations that took into account a number of beneficiaries such as: children in difficulty, the elderly, people with disabilities, users of banned substances and victims of domestic violence. Social services are mainly aimed at people who are in an unfavorable social situation and who cannot have a basic basis for their lives or who urgently need help for other serious reasons. The COVID-19 pandemic has had a negative impact on social services, with massive outbreaks being reported in all care facilities around the world, affecting not only residents, but also caregivers and visitors .